2018
DOI: 10.3892/ol.2018.8485
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin‑induced non‑canonical endocytosis of EGFR via p38 phosphorylation of the C‑terminal region containing Ser‑1015 in non‑small cell lung cancer cells

Abstract: Abstract. The aberrant activation of receptor tyrosine kinases (RTKs) is associated with tumor initiation in various types of human cancer, including non-small cell lung cancers (NSCLCs). Tyrosine kinase-independent non-canonical RTK regulation has also been investigated in tumor malignant alterations, including cellular stress responses. It was recently reported that the phosphorylation of epidermal growth factor receptor (EGFR) at C-terminal Ser-1015 serves a critical role in growth factor and cytokine signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…We confirmed that p38, a member of the MAPK cascade, is indeed activated during SOF treatment and translocated into the nucleus. Interestingly, the role of p38 in the regulation of EGFR in response to stress stimuli was shown by several groups [32,33,51]. However, we could demonstrate that the inhibition of p38 had no effect on the increased activation of EGFR observed during the exposure of cells to SOF, which excludes p38 as a driver of EGFR activation in this context.…”
Section: Discussionmentioning
confidence: 57%
“…We confirmed that p38, a member of the MAPK cascade, is indeed activated during SOF treatment and translocated into the nucleus. Interestingly, the role of p38 in the regulation of EGFR in response to stress stimuli was shown by several groups [32,33,51]. However, we could demonstrate that the inhibition of p38 had no effect on the increased activation of EGFR observed during the exposure of cells to SOF, which excludes p38 as a driver of EGFR activation in this context.…”
Section: Discussionmentioning
confidence: 57%
“…We looked at RCP tyrosine phosphorylation as cisplatin has been shown to increase tyrosine phosphorylation EGFR in cancer cells 51 , but our p-tyrosine pulldowns did not show any tyrosine phosphorylation on RCP. Cisplatin has also been shown to regulate serine phosphorylation of EGFR, leading to internalisation of EGFR, which was independent of tyrosine phosphorylation 52 . Whether or not RCP is phosphorylated upon chemotherapeutic exposure remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The transfected cells were then cultured under either normoxic or hypoxic conditions. Western blotting results showed that the protein expression levels of EGFR, in addition to the autophosphorylation of one of its most important residues, Tyr1068 (28,29), were shown to be significantly increased in the LV-mdig group compared with those in the LV-con group (P<0.05). These two aforementioned parameters were found to be significantly reduced in the LV-mdig-RNAi group compared with those in the LV-mdig-RNAi-con group (P<0.05; Figs.…”
Section: Mdig Promotes the Protein Expression Of Egfr And P-egfrmentioning
confidence: 95%